Trigger finger management, comparison of conservative and surgical treatment approach in hospital decision making: a case report - Anak Agung Ngurah Bayu Putra; Anak Agung Ngurah Ronny Kesuma (DiscoverSys Inc., 2019)
Introduction: Trigger fingers are conditioned as the inability of the digit to move flex and extend caused by inflammation in the proximal edge of the flexor tendon pulley, such condition will have an impact on daily living activity and functional activity of person. Aim of this report is to give an overview regarding trigger finger clinical presentation with approach management in clinical setting.Case Presentation: A 39-old male come to the policlinic with complaint stiffness in right middle finger, on physical examination finding the middle finger on the right hand is locking in flexed position, tenderness palpation over the A1 pulley.Conclusion: Trigger finger is condition inability the digit can’t move smoothly in flexed and extended. The management of trigger finger is based on Quinnell classification, after grading the treatment divided with conservative treatment or surgical treatment and both of treatment have success rate and complication rate.